Homology Modeling Studies of Yeast Mitogen-Activated Protein Kinases (MAPKS): Structural Motifs as a Basis for Specificity - Smith, D.L.; Nilar, S.H. (Protein and Peptide Letters, 2010)
Mitogen-activated protein kinases (MAPKs) are key components of cellular signal transduction. It is the objective of this communication to demonstrate that insight into protein-protein interactions in the Common Docking motif of yeast mitogen-activated protein kinases can be obtained based on homology models. Homology models for four yeast MAPKs, FUS3, KSS1, HOG1 and MPK1 were built based on the X-ray structures of active and inactive rat ERK2. The structural motifs required for the basis of specificity were rationalized based on these structures.
Keywords: Homology